Complications and mishaps in anesthesia : Cases - analysis - preventive strategies - Koch, Thea; Domino, Karen B.; Hubler, Matthias (Springer Berlin Heidelberg, 2014)
Ability to learn from errors is an essential aspect of the quest to improve treatment quality and patient safety. This book consists of 33 cases in anesthesiology that are based on real life situations and illuminate avoidable complications and mishaps. The cases are presented in a novel manner in that they are embedded within narratives. The reader comes to each case "cold", without any clue as to the content, and each case comprises a narrative and a factual component that are interwoven. The narrative parts provide the reader with information and tips regarding the clinical problems and tasks that the protagonist must face and try to solve. The idea is to engage the reader emotionally while reading and to entertain him or her while learning. All cases conclude with short debriefing sections which include possible strategies to prevent similar errors or mishaps.